Menstrual-cycle and hormonal-contraceptive tracking in Gaelic football: From the lab to the field - Taim, B. C.; Ó Catháin, C.; Elliott-Sale, K. J.; Madigan, S.; Ní Chéilleachair, N. (International Journal of Sports Physiology and Performance, 2025)
Purpose The purpose of this study was to describe the implementation of menstrual-cycle (MC) and hormonal-contraceptive (HC) tracking among Gaelic Football players, including the characterization of MC status and symptomatology, and to examine the effect of MC and oral-contraceptive-pill phases on daily wellness.